Impact of age at menarche on obesity and glycemic control in Japanese patients with type 2 diabetes: Fukuoka Diabetes Registry. Issue 5 (16th April 2018) - Sumi, Akiko; Iwase, Masanori; Nakamura, Udai; Fujii, Hiroki; Ohkuma, Toshiaki; Ide, Hitoshi; Jodai‐Kitamura, Tamaki; Komorita, Yuji; Yoshinari, Masahito; Kitazono, Takanari
Abstract: Aims/Introduction: A younger age at menarche is associated with obesity and type 2 diabetes in adult life. The impact of early‐onset menarche on obesity and glycemic control in type 2 diabetes has not been investigated. The present study examined the relationship between age at menarche and obesity and glycemic control in type 2 diabetes. Materials and Methods: A total of 2, 133 patients with type 2 diabetes aged ≥20 years were divided into groups according to age at menarche (≤11, 12, 13, 14 and ≥15 years). A retrospective cohort study examined the association of menarcheal age with adiposity and hemoglobin A1c . Results: Age at menarche was inversely associated with body mass index (BMI) and abdominal circumference ( P < 0.001). Each 1‐year decrease in age at menarche was associated with a 0.25‐kg/m 2 and 0.6‐cm increase in BMI and abdominal circumference, respectively, using a multivariate‐adjusted model. Odds ratios for obesity and abdominal obesity significantly increased in participants with age at menarche ≤11 years after multivariable adjustments when age at menarche of 13 years was used as the reference (odds ratio 1.95, 95% CI 1.33–2.88, odds ratio 1.95, 95% CI 1.32–2.87, respectively). Younger age at menarche was significantly associated with higher hemoglobin A1c ( P < 0.001); however, the association was not statistically significant after adjusting for BMI. Conclusions: Age at menarche of ≤11 years was associated with obesity after adjusting for confounding factors, and poor glycemic control associated with high BMI in type 2 diabetes. Age at menarche should be considered during clinical assessments. Abstract : Age at menarche was inversely associated with obesity after adjusting for confounding factors, and poor glycemic control associated with BMI in type 2 diabetes.